Could socks play an active role in ankle sprain prevention? A preliminary investigation - Torres, Rui M.; Mesquita, Inês (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Ankle sprain represents about 10% to 30% of all recorded musculoskeletal injuries, and is one of the most prevalent injuries in sports. Thus, any type of intervention based on prevention is extremely important to reduce its incidence. Aim of Study. To compare the immediate effect of three different types of socks, namely standard, compression, and Prevent Sprain Technology (PST) socks, on the dynamic unipodal balance and ankle joint position sense in healthy participants. Material and Methods. Forty-two healthy adults, aged 20.34 ± 1.69 years old, volunteered to participate in the study. Participants were randomly assessed using three different sock models. The main measured outcomes selected for this study were the dynamic balance using the Biodex Balance System®, and the active ankle joint repositioning movement through the Biodex System Pro 4®. We used the Friedman test to compare the variables under study among the three conditions, with Dunn’s post-hoc analysis and a significance level of 0.05. Results. In the Biodex Balance System® the participants had a lower Global Instability Index value with the PST socks compared to compression socks (p = 0.031), and standard socks (p = 0.005), but only lower anteroposterior (p = 0.042) and mediolateral (p = 0.026) instability indices when compared to standard socks. Regarding the ankle joint position sense, subjects with PST socks revealed lower absolute errors compared to standard socks (p = 0.007), smaller minimum errors compared to compression socks (p = 0.049), and smaller maximum errors compared to compression socks (p = 0.049) and standard socks (p = 0.008). Analysis of relative errors revealed a significant miss regarding the target joint position at higher inversion angles only with standard socks (which is potentially more dangerous) when compared to PST socks (p = 0.031), which error tends to be at lower inversion angles (which is potentially less dangerous). Conclusions. The PST socks seem to have a global positive influence on the mechanisms underlying the dynamic unipodal balance and active joint position sense, which could be an important tool for ankle sprain prevention.
Keywords: Prevent Sprain Technology socks; compressionsocks; proprioception; joint position sense; unipodal dynamic balance